1995
DOI: 10.1002/micr.1920160211
|View full text |Cite
|
Sign up to set email alerts
|

Experimental microvenous thrombosis following anastomosis with a knotted suture

Abstract: An experimental model for producing venous thrombosis was developed in end-to-end anastomoses of femoral veins in rats. The anastomoses were performed using a suture (9-0 suture-70 microns needle) with a knot 1 cm from the needle. The knot was formed by making either six or eight half-hitches in one throw of the suture. Vessel patency was assessed through the direct "milking test" at 20 min and 24 hrs. The incidence of thrombosis when using one knot with six half-hitches ranged from 20% to 40% and with eight h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In our model the animals were followed up for 8 to 12 postoperative weeks, which period was supposedly enough for the shunt maturation 11, 14. Although previous studies demonstrated patency rates differences between immediate after anastomosis, 20 min, 24 hours, and 7 days, and recanalization rate of thrombosed vessel in three weeks in rats,35–37 we wished to wait for a sufficient time for having mature shunts and compensated circulatory situations. Langer et al,20 using ultrasound‐based functional and morphometric analyses, demonstrated the fistula vein's alterations in rat distal femoro‐femoral AV anastomosis during the maturation period: on the 1st, 2nd, 3rd, 6th, 12th, and 20th postoperative weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In our model the animals were followed up for 8 to 12 postoperative weeks, which period was supposedly enough for the shunt maturation 11, 14. Although previous studies demonstrated patency rates differences between immediate after anastomosis, 20 min, 24 hours, and 7 days, and recanalization rate of thrombosed vessel in three weeks in rats,35–37 we wished to wait for a sufficient time for having mature shunts and compensated circulatory situations. Langer et al,20 using ultrasound‐based functional and morphometric analyses, demonstrated the fistula vein's alterations in rat distal femoro‐femoral AV anastomosis during the maturation period: on the 1st, 2nd, 3rd, 6th, 12th, and 20th postoperative weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The milking test subjectively revealed the occlusion of the vessel lumen and is related to the degree of anastomotic vessel constriction caused by thrombosis and affected mainly by the surgeon's skill. 13,24 Results of early and late milking tests were not compromised in any of the anastomoses (p > 0.05; Table 2). In terms of quality of filling, however, C suture technique was inferior compared with the other suture techniques.…”
Section: Anastomotic Leakage and Patencymentioning
confidence: 94%
“…2,5 Evaluation was performed by direct visual examination, by the milking test, 6 and by cutting the vein downstream to the anastomosis at 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…The influences upon patency of twisting the vessel's ends prior to anastomosis, 1 of wall mechanical damage, 2 of epigastric flap creation and distal femoral vessel ligation, 3 and of prolonged clamping and vascular stasis 4 have all been reported. To the best of the authors' knowledge, no experiment has been reported dealing specifically with the effects on vessel patency of what is probably the most common mistake in microsurgical anastomosis: the twowall stitch (TWS).…”
mentioning
confidence: 97%